Regulation capacity evaluation for air conditioners considering operating status and occupant comfort. Issue 1 (1st February 2022) - Yang, Xuan; Xu, Xianghai; Yin, Jianbing; Liu, Jian; Wei, Wei; Zhang, Zhipeng; Chen, Zhiyuan; Lu, Haibo; Qi, Taoyi; Xie, Kang
Abstract: In recent years, the load peak-valley difference is increasing rapidly and needs more regulation capacity to reduce it. However, traditional generating units are phasing out for low carbon goal and cannot provide enough regulation capacity for the power system. Besides, Air conditioners (ACs) account for about 40% of the electricity consumption of the power system during peak period in summer. Due to the thermal inertia of rooms, indoor temperature will not be greatly affected, when ACs are controlled temporarily to provide regulation capacity. To fully realize the regulation potential, it is of significantly importance to accurately evaluate the regulation capacity of ACs, where the real-time operating status and occupant comfort are two key factors. Therefore, this paper proposes a regulation capacity evaluation method for ACs considering operating status and occupant comfort. The equivalent thermal parameter (ETP) model based on the AC operating characteristics is developed firstly. On this basis, the regulation capacity for the individual AC is evaluated considering operating status and user comfort, and the regulation capacity of aggregated ACs can be obtained by summing. Finally, the effectiveness of the proposed method is proved by cases.